Identifikasi Jenis Lichen di Kawasan Objek Wisata Teluk Wang Sakti - Andrea, Eastu Septine; Zuhri, Rozana; Marlina, Leni (STKIP YPM Bangko, 2018)
This research was motivated by the lack of data on the types of lichen in the TelukWang Sakti Area and the research on the types of lichen in Merangin is verylacking. Lichen can be found in the Teluk Wang Sakti Area because it has naturalconditions that support lichen growth and development. The purpose of thisresearch was to find out and describe the types of lichen in Teluk Wang Sakti. Thistype of research used a qualitative descriptive research. The research method usedwas the method of reconassance (roaming). The location of the research wasconducted in Teluk Wang Sakti and on the edge of Jl. Lintas Bangko-Kerinci.Lichen found in Teluk Wang Sakti is 60 species including 11 genera and 10families : Parmotrema and Parmelia (Family Parmeliaceae),Graphis (FamilyGraphidaceae), Dichosporidium (Family Rosellaceae), Arthonia (FamilyArthoniaceae), Dirinaria (Family Dirinariaceae), Cryptothecia (FamilyCryptotheciaceae), Lecanora (Family Lecanoraceae), Megalospora (FamilyMegalosporaceae), Lepraria (Family Leprariaceae) and Caloplaca (FamilyCaloplacaceae). Teluk Wang Sakti Area has an average temperature of 27.9oC and82.3% humidity. While on the edge of Jl. Bangko-Kerinci crossing around thefactory has an average temperature of 42.2oC and humidity of 36%. The TelukWang Sakti Area is indicated to have better air quality compared to the edge of Jl.Bangko-Kerinci crossing around the factory, due to the lack of types of lichen foundand the presence of Parmotrema sp. type of lichen used as a bioindicator of airpollution.